Emission concerned economic dispatch considering carbon dioxide quota policy / Hanisah Abd Jalal - Abd Jalal, Hanisah (2011)
This thesis presents the mathematical formulation of economic dispatch problem in electricity market under emission concerned policy, which is carbon dioxide quota policy. The formulation using Lagrangian relaxation methods is presented in this thesis. An algorithm, which is developed using MATLAB, is proposed to solve economic dispatch problem considering the carbon dioxide quota policy. Data from four generators in IEEE 14-bus system are used in this formulation. By using the proposed algorithm, the results for the economic dispatch problem can be obtained and fulfil the quota policy. In this manner, the problem of emission of carbon dioxide can be reduced and controlled.